Inovasi Praktik Pekerjaan Sosial dalam Pelayanan Sosial Anak Pada Masa Covid-19: Studi di Dua Panti Rehabilitasi Sosial Anak di Jawa Barat - Susilowati, Ellya; Subardhini, Meiti; Herlina, Elin (Pekerjaan Sosial, 2021)
This study aims to describe innovations of social work practices in children’s social services carried out by social workers during the Covid-19 pandemic at the Child Social Rehabilitation Institution in West Java. This research was conducted qualitatively with the data collection techniques such as interviews, focus group discussions and documentary studies of social worker reports while paying attention to the health protocol. The informants involved in this study were five social workers at the Social Rehabilitation Center for Children who need Special Protection (PRSAMPK) in Subang and Garut. The results showed that there were innovations made by social workers in handling children during the COVID-19 pandemic in the assessment process, intervention planning, intervention implementation, evaluation and termination. However, social workers still have obstacles in optimizing innovative social work practices in providing social services during the Covid-19 pandemic. These obstacles include the increased frequency of workloads in handling children because the clients are in the instisutuion, the limited number of social workers and supporting facilities for children’s activities. The results of this study recommend that social workers begin to record their findings and successes in developing their innovations, so that they become learning materials for other social workers. Evidence best practices of social worker becomes a model in handling children during crisis situations in institutional settings.